The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4067/s0718-09342015000300006
|View full text |Cite
|
Sign up to set email alerts
|

Uso estratégico de representaciones pictóricas en un texto de ciencias con un detalle seductor en lectores con bajo conocimiento previo

Abstract: ResumenLa Teoría Cognitiva de Aprendizaje Multimedia (Mayer, 2001(Mayer, , 2005 sostiene que el procesamiento conjunto de información lingüística y pictórica resulta en una representación mental integrada del mensaje, y que la adición de representaciones pictóricas puede tanto beneficiar como perjudicar el desempeño asociado a la lectura, dependiendo de la función que cumplan dichos agregados. Este estudio examinó experimentalmente el efecto de asociar representaciones pictóricas con un texto expositivo en cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
5
0
3
Order By: Relevance
“…In contrast to the emotional design literature, Mayer (1997, 1998) and Mayer (2014) argued that increasing interest in learning materials through emotionally appealing but irrelevant illustrations would lead to pay more attention to the irrelevant images, which could also interrupt the reader's mental model construction, and so hinder comprehension. Indeed, including seductive images with decorative and emotional, but not informational value, has been associated with decreases in expository text comprehension, memory, and learning (e.g., Abercrombie et al 2019;Eitel et al 2019;Mayer 1997, 1998;Park and Lim 2007;Sanchez and Wiley 2006;Saux et al 2015;Strobel et al 2019;Wiley 2019). This replicated finding (see metaanalysis by Rey 2012) has been termed the seductive detail effect.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to the emotional design literature, Mayer (1997, 1998) and Mayer (2014) argued that increasing interest in learning materials through emotionally appealing but irrelevant illustrations would lead to pay more attention to the irrelevant images, which could also interrupt the reader's mental model construction, and so hinder comprehension. Indeed, including seductive images with decorative and emotional, but not informational value, has been associated with decreases in expository text comprehension, memory, and learning (e.g., Abercrombie et al 2019;Eitel et al 2019;Mayer 1997, 1998;Park and Lim 2007;Sanchez and Wiley 2006;Saux et al 2015;Strobel et al 2019;Wiley 2019). This replicated finding (see metaanalysis by Rey 2012) has been termed the seductive detail effect.…”
Section: Introductionmentioning
confidence: 97%
“…This replicated finding (see metaanalysis by Rey 2012) has been termed the seductive detail effect. For example, in Saux et al (2015), a text explained a mechanism (how aerogels work), with or without a picture depicting the person who invented it. College students remembered less about the mechanism when the picture was included.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later research, however, came to conclusions that partially contradicted those results. Although some studies found the schema activation effect (manipulating detail location) (Rowland et al, 2008;Saux et al, 2015), others did not (Lehman et al, 2007;Mayer et al, 2001). Additionally, the distraction hypothesis (Chang & Choi, 2014;Lehman et al, 2007;Sanchez & Wiley, 2006) and disruption hypothesis (Lehman et al, 2007;Mayer et al, 2008;Park, Moreno, Seufert, & Brünken, 2011;Schnotz, Fries, & Horz, 2009) gained support.…”
mentioning
confidence: 99%
“…El tipo de imágenes que aparecen en los textos va a favorecer o no la comprensión, por esto es importante que se primen el uso de imágenes efectivas en detrimento de las imágenes seductoras e irrelevantes que pueden llevar a confusiones, principalmente a los alumnos con un nivel bajo de conocimientos previos. Como señalan Saux et al (2015) a la hora de incluir imágenes en los textos se tienen que tener en cuenta no solo criterios formales, editoriales o publicitarios, si no especialmente psicológicos.…”
Section: Analizar Las Imágenes Y Las Representaciones Visualesunclassified